Struktur Komunitas Epifauna di Area Pasca Budidaya Rumput Laut di Kabupaten Badung Bali - Rizqi, Mohammad; Arthana, I Wayan; Sari, Alfi Hermawati Waskita (Current Trends in Aquatic Science; Vol 4 No 1 (2021), 2021)
Pandawa and Geger Beaches used to be seaweed farming areas, later became tourist attractions which resulted in changes in the structure of the epifauna community. This study aims to determine the community structure and water quality at both beaches. The study was conducted from December 2018 to January 2019. Descriptive method was used and the determination of stations us ed purposive sampling. The sample was taken by the line transect method. The highest abundance of Pandawa Beach epifauna was Diadema setosum (0.444 ind / m2). The highest diversity at the seaweed cultivation area station with a value of 1.105 which belongs to the medium category. The highest uniformity was also in the same station with a value of 0.797 which indicate a stable epifauna community. The highest dominance in the tourist area station with a value of 0.861 which indicates high dominance. At Geger Beach the highest abundance of epifauna was Cerithidea obtusa species and Tripneustes gratilla with the same abundance (0.144 ind / m2). The highest diversity at the station adjacent to the coral pool with a value of 1,944 included in the medium category. The highest uniformity at the same station with a value of 0.935 which indicates a stable epifauna community. The highest dominance was obtained at the station near the pier with a value of 0.229 which showed low dominance. Pandawa and Geger Beach es water quality was still relatively optimal with an average temperature, dissolved oxygen, salinity, currents, and pH of 30.5 o C; 5.4 ppm; 30.3 ppt; 0.1 m/s; and 8.6 respectively. At Geger Beach, the average temperature, dissolved oxygen, salinity, current and pH were 30.6 o C; 5.1 ppm; 30.1 ppt; 0.1 m/s; and 8.7 respectively.